Evaluation of micro leakage in composite restoration by using self etch and total etch adhesive agents after using 35% carbamide peroxide bleaching gel - F Sharafeddin; MY Varachehre (Isfahan University of Medical Sciences, 2008)
Introduction: Bleaching gel may increase micro leakage in composite restorations. Also by using proper adhesive agents, micro leakage will be reduced. The aim of this study was to evaluate the micro leakage of composite restoration by using self etch and total etch (fifth, sixth and seventh generation) of adhesive agents after using 35% carbamide peroxide gel.Methods and Materials: After preparation of CLV cavity in the buccal and lingual surface of 30 extracted bovine teeth, the teeth were divided to six groups. (n = 5) Then one of the adhesive agents, Single bond (self etch, groups 1 and 4), prompt L- POP (total etch, groups 2 and 5), G Bond, (Self etch Group 3 and 6) were used in the cavity and then restored with Z100 composite. Then groups 4, 5 and 6 were exposed to 35% carbamide peroxide gel three times for 30 minutes each time. The specimens were termocycled in 5 ± 2◦C and 55 ± 2◦C c for 500 times and stored in basic fusing for 24 hours. Then the teeth were sectioned and dye penetration was evaluated by Stereomicroscope (× 40). The results were analyzed by suing kraskal- wallis and Man- whithny tests (α < 0.05). Results: Ther was no significant difference in micro leakage after using different adhesive and 35% carbamid peroxide bleaching gel (p value =0.63). Micro leakage in gingival margin was higher than incisal margin (P value = 0.037).Conclusion: By using total etch and self etch (5th, 6th, 7th generation) of adhesive agents and 35% cabamid peroxide gel, micro leakage was similar and micro leakage in gingival margin was higher than incisal margin.Key word: Adhesive agent, Bleaching gel, Composite, Micro leakage